2020
DOI: 10.1016/j.psj.2019.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of curcumin on laying performance, egg quality, endocrine hormones, and immune activity in heat-stressed hens

Abstract: This study was conducted to evaluate the effect of curcumin on laying performance, egg quality, biochemical indicators, hormone levels, and immune activity in hens under heat stress. Hy-Line brown hens (280-day-old) were fed with 0, 100, 150, and 200 mg/kg of curcumin during a 42-D experiment. Compared with the control treatment, supplementation with 150 mg/kg of curcumin improved laying performance and egg quality by significantly increasing egg production, eggshell thickness, eggshell strength ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 35 publications
6
86
1
2
Order By: Relevance
“…This however could not be attributed to treatment conditions as the results were not signi cantly affected across all groups. Similarly, a laying rate of 74.74% at 40 to 46 weeks [46] and 86.2% from 21 to 35 weeks of age, had been reported from previous studies [47].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This however could not be attributed to treatment conditions as the results were not signi cantly affected across all groups. Similarly, a laying rate of 74.74% at 40 to 46 weeks [46] and 86.2% from 21 to 35 weeks of age, had been reported from previous studies [47].…”
Section: Discussionsupporting
confidence: 82%
“…Curcumin was demonstrated to improve antioxidant status in heat-stressed hens by lowering serum MDA levels while promoting enzymatic activities of SOD and GSH-Px [46]. Our study revealed that MDA levels were reduced, whereas anti-oxidants such as CAT, SOD, and T-AOC were elevated in laying hens fed L-Cit.…”
Section: Anti-oxidant Statusmentioning
confidence: 54%
See 1 more Smart Citation
“…The relationship between these measures of egg quality demonstrates that L-Cit increment of egg external shape index may correspond to improved egg internal quality. Similar to our findings, dietary supplementation with natural antioxidants (thyme, oregano, curcuma longa and rosemary) increased egg shape index of laying hens (64).Liu et al(65) reported that increased circulating free calcium (Ca 2+ ) in the blood in combination with other plasma proteins which are involved in egg shells formation resulted in improved egg shell quality. Likewise, there exist a quantitative relationship between calcium concentrations and citrulline synthesis in the mitochondrial matrix(66).…”
supporting
confidence: 86%
“…Increased activity of antioxidant enzymes has been associated with decreased MDA levels (84). Likewise, curcumin was shown to improve antioxidant status in heat stressed hens by lowering serum MDA levels while promoting enzymatic activities of SOD and GSH-Px (65).…”
Section: Anti-oxidant Statusmentioning
confidence: 99%